Novel DNMT3B Mutation in a Patient with Immunodeficiency, Centromeric Instability, and Facial Anomalies (ICF) Syndrome and a Bronchopulmonary Collateral Artery - Aminorroaya, Arya; Rayzan, Elham; Shahkarami, Sepideh; Seyedpour, Simin; Zoghi, Samaneh; Aryan, Zahra; Somekh, Ido; Rohlfs, Meino; Klein, Christoph; Esmaeilzadeh, Hossein; Rezaei, Nima (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Immunodeficiency, centromeric instability, and facial anomalies (ICF) syndrome is a rare autosomal recessive disorder. ICF1 is caused by bi-allelic mutations in the gene encoding deoxyribonucleic acid methyltransferase-3B (DNMT3B). Herein, we report a novel homozygous DNMT3B mutation in a patient with ICF1. Case Presentation: An eight-month-old Iranian Caucasian infant of consanguineous 1st-degree cousins presented to our clinic for evaluation of neutropenia. Physical examination was unremarkable except for low-set ears and a systolic cardiac murmur. He had a history of recurrent respiratory infections and oral thrush. Moreover, a collateral artery between the bronchial and pulmonary arteries was observed on the angiogram, mimicking a patent ductus arteriosus on the echocardiogram. Growth percentiles were normal; however, he had a neurodevelopmental delay. Family history was significant for a sibling who deceased at nine months of age after recurrent respiratory infections. Laboratory evaluation revealed a normal white blood cell count with neutropenia and normal bone marrow studies. He had hypogammaglobinemia with normal flow cytometric studies and was treated with prophylactic trimethoprim-sulfamethoxazole and itraconazole. After that, he was re-admitted three times due to recurrent episodes of pneumonia and an episode of pseudomonas aeruginosa meningitis. Currently, he is five years old and doing well on monthly intravenous immunoglobulin. Due to recurrent infections, hypogammaglobulinemia, and neutropenia, as well as a family history of consanguinity and a sibling who deceased during infancy, a primary immune deficiency was suspected. Genetic studies utilizing whole-exome sequencing demonstrated a homozygous missense mutation in DNMT3B (LRG_56t1:c.2008C>T; p.Arg670Trp) in the patient studied. The mutation has not been previously reported. Conclusion: We describe a novel homozygous DNMT3B mutation in an Iranian boy with ICF1. It is associated with recurrent infections, hypogammaglobinemia, neutropenia, mild facial anomalies, and a bronchopulmonary collateral artery.
Keywords: congenital